Improving the Sales Process on the Website of Haviland House Joint Stock Company - Tran, Thi Ngoc Duyen (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - E-commerce Management; 2021-2025.